Measures of resting state EEG rhythms for clinical trials in Alzheimer's disease: Recommendations of an expert panel. Issue 9 (15th April 2021) - Babiloni, Claudio; Arakaki, Xianghong; Azami, Hamed; Bennys, Karim; Blinowska, Katarzyna; Bonanni, Laura; Bujan, Ana; Carrillo, Maria C.; Cichocki, Andrzej; de Frutos‐Lucas, Jaisalmer; Del Percio, Claudio; Dubois, Bruno; et al.
Abstract: The Electrophysiology Professional Interest Area (EPIA) and Global Brain Consortium endorsed recommendations on candidate electroencephalography (EEG) measures for Alzheimer's disease (AD) clinical trials. The Panel reviewed the field literature. As most consistent findings, AD patients with mild cognitive impairment and dementia showed abnormalities in peak frequency, power, and "interrelatedness" at posterior alpha (8‐12 Hz) and widespread delta (< 4 Hz) and theta (4‐8 Hz) rhythms in relation to disease progression and interventions. The following consensus statements were subscribed: (1) Standardization of instructions to patients, resting state EEG (rsEEG) recording methods, and selection of artifact‐free rsEEG periods are needed; (2) power density and "interrelatedness" rsEEG measures (e.g., directed transfer function, phase lag index, linear lagged connectivity, etc.) at delta, theta, and alpha frequency bands may be use for stratification of AD patients and monitoring of disease progression and intervention; and (3) international multisectoral initiatives are mandatory for regulatory purposes.